Pesticide Monitoring Program: Design Assessment. (11th February 2015) - ,; ,
Abstract: The objective of the EU‐coordinated Multi Annual Pesticide Control Program (MACP) is the assessment of MRL exceedance (above 1%) in food items available for consumption in the EU market as well as consumer exposure. The 30 food items currently included in the survey represent 70% of the consumption of adults and around 74% of consumption by children. Probability based sampling methods minimize selection bias, since every element in the population of food items has a non‐zero probability of being selected. Using a stratified sampling framework based on food consumption, MRL‐exceedance could be estimated with a margin of error of 0.0075 (in terms of raw proportion) by selecting 683 sample units for 32 different food items. The participating countries can be considered to constitute strata since sampling is organized within the countries themselves, for each food item the 683 sample units can be proportionally allocated either on the basis of the resident population or the food item consumption, producing different allocations, the latter being the recommended option. A sample size of 683 is also sufficient to ensure that assessment of consumer exposure is achieved with the same margin of error and confidence. Based on a review of the characteristics of the EU‐coordinated multiannual control programme and the use of probability based sampling methods 21, 856 samples would need to be taken. This could be split over a three year period. A survey sample design approach requires high quality food consumption data at the level of individual food items for all reporting countries. Food consumption data for individual food items covering all reporting countries should be collected and assessment related to the selection of food items should be revised as well as the allocation of samples per Member States according to the new consumption figures.